2018
DOI: 10.5005/jp-journals-10069-0042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Epworth Sleepiness Scale and STOP-BANG Questionnaire for Diagnosing Obstructive Sleep Apnea at a Tertiary Care Centre in North India: A Retrospective Study

Abstract: Introduction:The diagnosis of obstructive sleep apnea (OSA) requires polysomnography (PSG). The screening of OSA utilizes questionnaires like the Epworth sleepiness scale (ESS) and the STOP-BANG questionnaire (SBQ) that have variable predictive value, as reported from the Western literature. Materials and methods: A retrospective cohort study was done in adult subjects (n = 80) presenting with symptoms of OSA. The demographic profile, ESS, and SBQ scores were evaluated. The level one recorded PSG was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Included studies showed low to moderate risk of bias after validity assessment and were used to answer our review question. Studies were organized into 6 groups: (1) North America (9 studies, [19][20][21][22][23][24][25][26][27] 3507 participants); (2) South America (6 studies, [28][29][30][31][32][33] 3) Europe (10 studies, [34][35][36][37][38][39][40][41][42][43] 5679 participants); (4) the Middle East (11 studies, [44][45][46][47][48][49][50][51][52][53][54] 3468 participants); (5) East Asia (4 studies, [55][56][57][58] 1665 participants); and (6) South or Southeast Asia (7 studies, [59][60][61][62][63][64]…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Included studies showed low to moderate risk of bias after validity assessment and were used to answer our review question. Studies were organized into 6 groups: (1) North America (9 studies, [19][20][21][22][23][24][25][26][27] 3507 participants); (2) South America (6 studies, [28][29][30][31][32][33] 3) Europe (10 studies, [34][35][36][37][38][39][40][41][42][43] 5679 participants); (4) the Middle East (11 studies, [44][45][46][47][48][49][50][51][52][53][54] 3468 participants); (5) East Asia (4 studies, [55][56][57][58] 1665 participants); and (6) South or Southeast Asia (7 studies, [59][60][61][62][63][64]…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Study characteristics and demographic data are summarized in Table 1 and eTable 3 in the Supplement, respectively . The initial search yielded 3871 studies, with 162 additional studies identified through citations (eFigure 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations